2020
DOI: 10.1177/1470320320919586
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association study of prolylcarboxypeptidase polymorphisms with susceptibility to essential hypertension in the Yi minority of China: A case–control study based on an isolated population

Abstract: Objective: Prolylcarboxypeptidase (PRCP) is a negative regulator of the pressor actions of the renin–angiotensin–aldosterone system. It is also involved in the kallikrein–kinin system. This gene has an important role in blood pressure (BP) regulation. Methods: A case–control study was performed for 615 Yi participants (303 cases and 312 controls) from a remote mountainous area in Yunnan Province of China. For the PRCP gene, 11 tag single-nucleotide polymorphisms were genotyped using the polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…PRCP polymorphism (E112D) is associated with hypertension, and its expression is reduced in renovascular hypertensive rats ( 80 ). Recently, a novel polymorphism (rs12290550) was found to be associated with essential hypertension in a discrete Chinese ethnic group ( 72 ). PRCP gene trap mice (PRCP gt/gt ) constitutively have a small, but significant, increase in blood pressure.…”
Section: Angiotensin II and Coronavirus Infection: Is There A Causal mentioning
confidence: 99%
“…PRCP polymorphism (E112D) is associated with hypertension, and its expression is reduced in renovascular hypertensive rats ( 80 ). Recently, a novel polymorphism (rs12290550) was found to be associated with essential hypertension in a discrete Chinese ethnic group ( 72 ). PRCP gene trap mice (PRCP gt/gt ) constitutively have a small, but significant, increase in blood pressure.…”
Section: Angiotensin II and Coronavirus Infection: Is There A Causal mentioning
confidence: 99%
“…The study samples were selected according to the method reported previously. 7,23 The cases were diagnosed with EH according to the World Health Organization criteria for hypertension (systolic BP ⩾ 140 mm Hg and/or a diastolic BP ⩾ 90 mm Hg) and participants with secondary hypertension and other serious diseases were removed from this study. The controls with BP < 140/90 mm Hg had no history of hypertension and chronic diseases who were randomly chosen based on comparable gender and age matching hypertensive subjects.…”
Section: Subjectsmentioning
confidence: 99%
“…The PCR amplification protocol, length of target fragments and related restriction endonuclease are followed by a previously study. 23…”
Section: Snp Selection and Genotype Determinationmentioning
confidence: 99%